Autumnal leaf senescence in Miscanthus × giganteus and leaf [N] differ by stand age - Boersma, Nicholas N (Journal of experimental botany, 2015)
© The Author 2015. Published by Oxford University Press on behalf of the Society for Experimental Biology.